Gap Analysis of Competency-Based Work Training Programs at the UPTD BLK of Buleleng District - Budiani, Ni Kadek; Widiastini, Ni Made Ary; Suwena, Kadek Rai (Dinasti Publisher, 2026)
This study aims to analyze the gap in competency-based job training programs at the UPTD BLK of Buleleng Regency in improving the quality of human resources in accordance with industry needs. The background of this research is the mismatch between workforce competencies and the increasingly dynamic demands of the labor market. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that the planning of training programs has not been fully based on sustainable industry needs. Instructor competencies are generally adequate, but still require improvement in adapting to technology and applying innovative learning methods. Training facilities are considered sufficient; however, they have not fully met modern industry standards. In addition, strategies to enhance human resource quality need to be strengthened, particularly in building partnerships with the business and industrial sectors (DUDI). The SWOT analysis reveals strengths in government support, weaknesses in limited facilities and lack of industry synergy, opportunities in the growing demand for skilled labor, and threats from increasing labor competition and rapid technological advancements.